Engaging with Play and Graduate Writing Development - Brittany Amell; Eve-Marie C. Blouin-Hudon (Discourse and Writing/Rédactologie, 2018)
We begin by situating this work and ourselves in graduate writing. Although our experiences as burgeoning researchers are not a focus of this article, we are nonetheless present in the background, not unlike a palimpsest. We trace one aspect of this palimpsest—the use of playful and creative methods to generate ideas for this paper—before then suggesting three key concepts we consider foundational to discussions about play and graduate writing development. These are play, playspace, and mindsets. Building on these concepts, we offer some concluding remarks about the ambivalence some learners may have—which we refer to as play ambivalence—and propose that this ambivalence is partly related to the three concepts underscored in this article. We suggest that future research in play and graduate writing development could better consider this play ambivalence.